2022
DOI: 10.3390/cells11020274
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Concepts in Magnetobiology after 40 Years of Research

Abstract: This review contains information on the development of magnetic biology, one of the multidisciplinary areas of biophysics. The main historical facts are presented and the general observed properties of magnetobiological phenomena are listed. The unavoidable presence of nonspecific magnetobiological effects in the everyday life of a person and society is shown. Particular attention is paid to the formation of theoretical concepts in magnetobiology and the state of the art in this area of research. Some details … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 77 publications
1
28
0
Order By: Relevance
“…There is a considerable amount of research investigating magnetic field effects on biological functions 23,[59][60][61][62][63][64][65][66][67] . In the following, we review the effects of low-intensity magnetic fields on biology.…”
Section: Magnetosensitivity In Biologymentioning
confidence: 99%
“…There is a considerable amount of research investigating magnetic field effects on biological functions 23,[59][60][61][62][63][64][65][66][67] . In the following, we review the effects of low-intensity magnetic fields on biology.…”
Section: Magnetosensitivity In Biologymentioning
confidence: 99%
“…As is believed, MF can cause various, including toxic, effects in organisms [Ghodbane et al, 2013]. The difficulty lies in the fact that there is no convincing physical mechanism that would provide a discernible shift in the probability of an individual act of a chemical reaction in the MF on the order of the geomagnetic field, about 50 µT [Binhi and Rubin, 2022]. One of the mechanisms relates the biological effect of MFs to the presence of magnetic nanoparticles in organisms [Kirschvink et al, 1985;Binhi and Chernavsky, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to magnetoreception which normally functions under the typically-experienced physiological GMF that ranges in strength from ∼ 24 to 66 μT ( Alken et al, 2021 ), bioeffects induced by magnetic fields outside this intensity range on organisms have also been extensively explored ( Miyakoshi, 2005 ; Saunders, 2005 ; Ghodbane et al, 2013 ; Zhang et al, 2017 ; Tian and Pan, 2018 ; Binhi and Rubin, 2022 ). A magnetic field that is significantly reduced is usually termed a hypomagnetic field (HMF).…”
Section: Introductionmentioning
confidence: 99%
“…The manipulated HMF is frequently used in mimicking magnetic field intensity during deep space flight or celestial exploration ( Binhi and Prato, 2017 ; Zhang Z. et al, 2021 ), working as the sham or manipulated treatment group for research into bioeffects induced by changes in field intensity, magnetoreception mechanisms ( Fedele et al, 2014a ; Binhi and Prato, 2017 ) and paleomagnetic studies ( Qin et al, 2020 ). Bioeffects of HMFs have been a topic of considerable investigation ( Wan et al, 2014 ; Wan et al, 2015 ; Binhi and Prato, 2017 ; Tian and Pan, 2018 ; Wan et al, 2020b ; Zhang and Tian, 2020 ; Zhang Z. et al, 2021 ; Xue et al, 2021 ; Binhi and Rubin, 2022 ), with demonstrated effects on embryogenesis ( Fesenko et al, 2010 ), development ( Mo et al, 2012 ), reproduction ( Wan et al, 2014 ; Wan et al, 2015 ), cytoskeleton structure ( Mo et al, 2016 ), nervous system dysfunction and related behavioral outputs ( Choleris et al, 2002 ; Zhang et al, 2004 ; Binhi and Sarimov, 2009 ), circadian clockwork ( Bliss and Heppner, 1976 ; Fedele et al, 2014a ), migratory regulation ( Wan et al, 2015 ; Wan et al, 2016 ), and reactive oxygen species levels ( Sherrard et al, 2018 ; Zhang B. et al, 2021 ). However, the specific mechanisms and signaling pathways underlying phenotypic responses to the HMF remain poorly understood ( Binhi and Prato, 2017 ; 2018 ).…”
Section: Introductionmentioning
confidence: 99%